Analisis Peningkatan Prestasi Belajar Matematika Siswa dengan Pemberian Motivasi Berupa Reward pada Kelas IV SDN Maospati 1 Magetan (Eduscotech, 2025)
Learning motivation is one of the key factors that can influence students' academic achievement. One way to increase learning motivation is through the provision of rewards during the teaching and learning process. This study aims to determine students’ academic achievement through the provision of motivation in the form of rewards in mathematics learning for Grade IV students at SDN Maospati 1 Magetan in the 2023/2024 academic year. The approach used in this study is a descriptive approach, while the type of research is qualitative. The study was conducted at SDN Maospati 1 Magetan. Data collection techniques included observation, interviews, and documentation. The data analysis technique used in this study was interactive analysis, which includes data reduction, data presentation, and drawing or verifying conclusions. Based on the results of the study, it was found that providing motivation in the form of rewards in mathematics learning had a positive impact on students. Student achievement was considered very high because students had their own motivation to participate in mathematics learning. Only 3 students scored below the minimum passing grade (KKM), which was set at 75. Therefore, the provision of learning motivation in the form of rewards for students should be further developed.